2017
DOI: 10.1186/s12955-017-0801-y
|View full text |Cite
|
Sign up to set email alerts
|

Joint awareness in posttraumatic osteoarthritis of the knee: validation of the forgotten joint score in long term condition after tibial plateau fracture

Abstract: BackgroundEvaluating patient-reported outcomes (PRO) in early osteoarthritis (OA) of the knee is difficult. Established measurement tools are focused on one of the two major patient groups in knee surgery: young, highly active patients, or older patients with advanced degenerative OA of the knee. Joint awareness in everyday life is a crucial criterion in measuring PRO. The purpose of this study was to validate a German version of the “Forgotten Joint Score” (FJS) in patients after surgical treatment of tibial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Just recently Baumann et al reported on a study group of 77 skiers after tibial plateau fractures in a long-term follow-up study. It was found out that the PROM-score “forgotten knee score (FJS)”, which had been measured initially at arthroplasty, also significantly correlates with osteoarthritic radiologic knee joint degeneration in fracture cases [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just recently Baumann et al reported on a study group of 77 skiers after tibial plateau fractures in a long-term follow-up study. It was found out that the PROM-score “forgotten knee score (FJS)”, which had been measured initially at arthroplasty, also significantly correlates with osteoarthritic radiologic knee joint degeneration in fracture cases [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past surgeon oriented outcome measurements such as the Tegner-, Lysholm- or Oxford-Score were widely accepted and established as the only clinical outcome measurement in knee surgery [ 4 , 5 ]. Other studies focused on return to sports after tibial plateau fractures [ 6 , 7 ] but overtime patient-reported outcome measurements have gained importance as well as tools for assessing the return to daily activity and working life [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is compiled for an older, physically less active patient population. However, recent studies have proven reliability in younger patients[ 12 , 13 , 17 - 19 , 34 ]. The FJS measures the patient’s ability to forget the joint in everyday life, which is seen as ultimate goal resulting in maximum patient satisfaction[ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found a mean FJS of 41.6 points in our patient population. Recently, Baumann et al [ 34 ] published a validation study on the FJS in long-term results of patients in a posttraumatic condition after tibial head fracture in 77 skiers. They found an increased joint awareness of 70.7 points in the FJS 9-13 years after injury.…”
Section: Discussionmentioning
confidence: 99%
“…The total score derived from the individual questions ranges from 0 to 100 with high scores indicating good outcome, i.e., a low level of joint awareness. The questionnaire has shown good reliability and validity in psychometric analyses [6, 18] and has been validated in German [2, 3] and English [18].…”
Section: Methodsmentioning
confidence: 99%